Pros and Cons of International Baccalaureate Teaching and Learning in School Education: A Collaborative Autoethnography on Learning How to Learn - Aryal, Arnav (A Bi-annual South Asian Journal of Research & Innovation, 2025)
Introduction: Nepal’s drive to improve quality, equity, and resilience in schooling intersects with a global search for pedagogies that move beyond rote learning. The International Baccalaureate (IB) offers inquiry-focused frameworks—the Primary Years Programme (PYP) and Middle Years Programme (MYP)—that emphasise concept-driven learning, the Learner Profile, and Approaches to Learning (ATL) skills designed to help students “learn how to learn.”Methods: Using collaborative autoethnography (CEA), I (IB MYP Year III student), in collaboration with my parents, generated and analysed two years of diaries, onsite observation notes, and family dialogues. Reflexive thematic analysis, member checks, and an audit trail supported trustworthiness.Results: Six themes emerged. (1) Inquiry as identity and agency—voice/choice and transdisciplinary connections became routine in PYP/MYP classrooms. (2) Assessment and feedback cultures—criterion-related rubrics clarified expectations, but task “bunching” elevated stress. (3) Community and relationships—teacher rapport and the Learner Profile reframed feedback as character-building. (4) Access, resources, and equity—rich facilities and clubs supported learning, while affordability raised concerns. (5) Transitions and curricular continuity—shared ATL vocabulary eased school moves, yet local differences in planning and calendars mattered. (6) Wellbeing and self-management—competitive chess served as a laboratory for time management, metacognition, and emotion regulation, with perceived (but context-dependent) transfer to academics. These experiences map closely to IB’s published aims for inquiry, ATL, and holistic growth. Findings converge with policy priorities in Nepal’s School Education Sector Plan (SESP) 2022/23–2031/32, suggesting low-cost, scalable levers: coordinated assessment calendars; ATL-infused feedback routines across subjects; and transition toolkits for families moving between IB schools.Conclusion: IB’s strongest contributions in this context were inquiry-driven agency, transparent criteria, and shared skills language; constraints clustered around workload peaks, uneven implementation, and affordability. Practical cross-pollination—adapting ATL routines and assessment design principles beyond IB—can extend benefits to more learners while aligning with national reform goals.